1968
DOI: 10.1021/jo01267a053
|View full text |Cite
|
Sign up to set email alerts
|

Aralkyl hydrodisulfides. VIII. Alkaline decomposition and its competition with nucleophiles

Abstract: By reexamination of the reaction of benzyl hydrodisulfide with potassium hydroxide another mechanism has proved favorable, that involving proton abstraction followed by elimination of the hydrodisulfide ion. When a decreased amount of potassium hydroxide was added to the hydrodisulfide, a mixture of benzyl polysulfides was formed, the formation of which is attributed to hydropolysulfide ion. Nucleophilic attack by cyanide ion appears to proceed competitively with alkaline decomposition in the reaction of benzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…In organic solvents, cyanide, amines, hydroxide, and halides react as bases rather than as nucleophiles, abstracting a proton from RSSH and promoting its decay. 103,495,541,542…”
Section: Protein Persulfidationmentioning
confidence: 99%
“…In organic solvents, cyanide, amines, hydroxide, and halides react as bases rather than as nucleophiles, abstracting a proton from RSSH and promoting its decay. 103,495,541,542…”
Section: Protein Persulfidationmentioning
confidence: 99%
“…The outer sulfur can react with cyanide, thiolates, sulfite [133,135], amines [136], hydroxide [137], and tertiary phosphines [138,139]. Persulfides and cyanide react to form the corresponding thiol and thiocyanate, which, in the presence of ferric ions, forms a colored complex that can be quantified spectrophotometrically.…”
Section: Chemistry and Biology Of Persulfidesmentioning
confidence: 99%
“…Depending on which sulfur is attacked, different products can be formed. The attack on the outer sulfur generates thiol and hydropolysulfides that evolve to elemental sulfur (Equations 17,18), while the attack on the inner sulfur yields polysulfides and H 2 S (Equation 19) [137]. The decay products are also likely to depend on steric effects and on the acidity of the leaving groups.…”
Section: Chemistry and Biology Of Persulfidesmentioning
confidence: 99%
“…The generation of − SCN from cyanolysis (Reaction 1) implies that CN − attacks the terminal sulfane 1 sulfur (assuming a single step process, which is not necessarily the case and discussed below). Previous studies have examined the reaction of other nucleophiles with hydropersulfides and reported that many factors can control the site of nucleophilic attack with both sulfur atoms being possible targets [for example, 50,51,52]. More recently Bailey and coworkers [53] generated an organic hydropersulfide and examined its reaction with various nucleophiles and bases in methylene chloride.…”
Section: Discussionmentioning
confidence: 99%